Can the Scapular Dyskinesis Test be Associated with Throwing Related Injuries During the Course of Collegiate Baseball Seasons? - Masaaki Tsuruike; Yohei Mukaihara; Todd S. Ellenbecker (International Journal of Sports Physical Therapy)
# Background